Tunable superstructures of dendronized graphene nanoribbons in liquid phase - Xu, Fugui; Yu, Chunyang; Tries, Alexander; Zhang, Heng; Klaeui, Mathias; Basse, Kristoffer; Hansen, Michael Ryan; Bilbao, Nerea; Bonn, Mischa; Wang, Hai I.; Mai, Yiyong (Journal of the American Chemical Society, 2019)
In this Communication, we report the first synthesis of structurally well-defined graphene nanoribbons (GNRs) functionalized with dendritic polymers. The resultant GNRs possess grafting ratios of 0.59-0.68 for the dendrons of different generations. Remarkably, the precise 3D branched conformation of the grafted dendrons affords the GNRs unprecedented 1D supramolecular self-Assembly behavior in tetrahydrofuran (THF), yielding nanowires, helices and nanofibers depending on the dimension of the dendrons. The GNR superstructures in THF exhibit near-infrared absorption with maxima between 650 and 700 nm, yielding an optical bandgap of 1.2-1.3 eV. Ultrafast photoconductivity analyses unveil that the helical structures exhibit the longest free carrier (3.5 ps) and exciton lifetime (several hundred ps) among the three superstructure systems. This study opens pathways for tunable construction of ordered GNR superstructures with promising optoelectronic applications.
CRIS-Team Scopus Importer:2023-03-27